Prescription drug monitoring program in Australia: a qualitative study of stakeholders' experiences and perceptions of a state-wide implementation - Emma Tay; Meredith Makeham; Andrew Hargreaves; Tracey-Lea Laba; Melissa Baysari (BMC, 2024)
Abstract Background Prescription Drug Monitoring Programs (PDMPs) are increasingly implemented across the globe with aims of managing and mitigating risks relating to high-risk prescription medicines. There is limited research focused on identifying strategies or processes for large-scale PDMP implementation. This study aimed to identify strategies perceived as necessary for successful state-wide implementation of a PDMP by exploring the experiences and perceptions of stakeholders responsible for the implementation in New South Wales (NSW), Australia: to identify (1) the drivers of implementation; (2) perceived strategies that worked well; (3) barriers to implementation; and (4) the elements needed for long-term success of SafeScript NSW. Methods This study used a qualitative descriptive design. Theoretical frameworks used to design interview questions and guide thematic analysis were the non-adoption, abandonment, scale-up, spread, and sustainability (NASSS) framework and Quadruple Aim framework. Participants were stakeholders responsible for PDMP implementation in NSW. Recruitment and data collection were completed between March and April 2022. Semi-structured interviews were audio-recorded and transcribed. Two researchers independently reviewed transcripts, generated codes from the data, and mapped these to each NASSS domain. They came together multiple times during data analysis to review the codes and grouped them into higher level themes via a discussion and consensus process. Themes were then organised according to the four objectives of the study. Results Eight interviews were conducted and analysed after which thematic saturation was reached. All participants had a common understanding of the perceived benefits and drivers for PDMP implementation. Participants outlined ten key ingredients for perceived successful state-wide implementation. Strong and iterative engagement with a large number of stakeholder groups was viewed as critical, as was targeting user experience, ongoing monitoring and evaluation. These were facilitated by a phased roll-out strategy. Participants identified some barriers to implementation, particularly around poor usability and user experience of the tool. Conclusions This is one of the first studies focused on strategies for what was perceived to be successful state-wide implementation of PDMP. Successful implementation requires significant time and resourcing, with the design and configuration of the technology being only one component of a multi-strategy process. Knowledge and insights gained from this study may be useful for other implementations of similar digital health tools in large-scale jurisdictions.